Acute exercise mobilizes NKT-like cells with a cytotoxic transcriptomic profile but does not augment the potency of cytokine-induced killer (CIK) cells - Zúñiga, Tiffany M.; Baker, Forrest L.; Smith, Kyle A.; Batatinha, Helena; Lau, Branden; Gustafson, Michael P.; Katsanis, Emmanuel; Simpson, Richard J. (Frontiers in Immunology, 2022)
CD3+/CD56+ Natural killer (NK) cell-like T-cells (NKT-like cells) represent <5% of blood lymphocytes, display a cytotoxic phenotype, and can kill various cancers. NKT-like cells can be expanded ex vivo into cytokine-induced killer (CIK) cells, however this therapeutic cell product has had mixed results against hematological malignancies in clinical trials. The aim of this study was to determine if NKT-like cells mobilized during acute cycling exercise could be used to generate more potent anti-tumor CIK cells from healthy donors. An acute exercise bout increased NKT-like cell numbers in blood 2-fold. Single cell RNA sequencing revealed that exercise mobilized NKT-like cells have an upregulation of genes and transcriptomic programs associated with enhanced anti-tumor activity, including cytotoxicity, cytokine responsiveness, and migration. Exercise, however, did not augment the ex vivo expansion of CIK cells or alter their surface phenotypes after 21-days of culture. CIK cells expanded at rest, during exercise (at 60% and 80% VO2max) or after (1h post) were equally capable of killing leukemia, lymphoma, and multiple myeloma target cells with and without cytokine (IL-2) and antibody (OKT3) priming in vitro. We conclude that acute exercise in healthy donors mobilizes NKT-like cells with an upregulation of transcriptomic programs involved in anti-tumor activity, but does not augment the ex vivo expansion of CIK cells.